IMPLEMENTASI PENDEKATAN SAINTIFIK PADA MATA PELAJARAN PAI: KELAS XI IPA 2 SMAN 1 CIPEUNDEUY - Rindiyani; Dede Supendi; Manpan Drajat (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The scientific approach is a learning approach using scientific principles. This means that students play a more active role in the classroom. This is in accordance with the 2013 curriculum which has designed all aspects of learning. Research objectives: (1) to determine scientific-based learning designs in Islamic religious education subjects for class XI IPA 2; (2) to find out the process of implementing scientific-based learning in Islamic religious education subjects in class XI IPA 2; (3) to find out the scientific-based assessment carried out by PAI teachers in Islamic religious education subjects in class XI IPA 2. This study used a descriptive qualitative method with interview research techniques, observation, documentation, and data validity testing techniques with source triangulation. The theory used is the educational regulation Regulation of the Minister of Education and Culture number 22 of 2016 concerning Learning Process Standards which consist of the learning design used, the process of implementing learning, and the assessment carried out by educators. The results of the study: (1) The learning design used by PAI teachers in class XI IPA 2 is in accordance with the 2013 curriculum, namely by using a scientific learning design; (2) The process of implementing scientific-based learning is not realized; 3) The assessment made by PAI teachers in class XI IPA 2 in PAI learning has not been fully achieved.